Educational Technologies in hybrid Nursing education (Research, Society and Development, 2021)
This article aims to describe some educational technologies in the hybrid teaching of Nursing with a view to developing student autonomy. It is a proposal for an experience report, with a qualitative descriptive approach on educational technologies in hybrid teaching in Nursing. This article is based on the following discussions: discipline planning and hybrid teaching; the virtual environment and the educational technologies that permeate Nursing education with respect for each student's learning pace, which requires a new attitude from the teacher. As a mediator, he must innovate, know the digital tools, know how to implement pedagogical practices and know the social reality of his students. In conclusion, it is understood that thinking about hybrid teaching in the field of Nursing is to emphasize the protagonism of the student with autonomy in a participatory and reflective way, requiring interdisciplinary teaching based on competences capable of understanding the demands of the current world, considering an integral formation of the learner subject. Willingness to innovate, know the digital tools, know how to implement pedagogical practices and know the social reality of its students.